Latent coronary artery disease among smokers and smokeless tobacco users: a cross-sectional study - Mishra, Dheerendra Kumar; Mishra, Nimisha; Kumar, Pradeep; Raghuvanshi, Gyanendra (International Journal of Research in Medical Sciences, 2018)
Background: Tobacco related mortality and morbidity and increase in developing country like India. WHO projected till 2020 India will accounts 15% of tobacco related mortality especially preventable causes of death e.g. cardiovascular disease. Active tobacco smoking is undoubtedly major risk factor for cardiovascular disease, but subjects use smokeless tobacco in dependence pattern is not extensively evaluated for cardiovascular risk factor. In India smokeless tobacco especially Khaini is major form of tobacco consumption. Scarcity of data on effects of smokeless tobacco in cardiovascular disease especially coronary artery disease major limiting factor for undermine the detailed evaluation of cardiovascular effects in smokeless tobacco dependence subjects. The aim of the study was to study the risk of coronary artery disease among smokeless tobacco dependence in comparison to tobacco dependence smokers. Methods: Cross-sectional assessments were done on 36 adults (>18 years), treatment-seeking patients with a ICD 10 diagnosis of Mental and behavioral disorders due to use of tobacco. Data was collected on socio-demographic characteristics, and after detailed clinical evaluation treadmill exercise test was done. Results: Mean age of tobacco dependence smokers 51.5±9.6 years vs 53.6±7.5 years. There were male predominant in study subjects and 38% subjects was treadmill test positive. Smokeless tobacco users had 35% positive treadmill test, and among Smokers 42% subjects was positive for treadmill test. Conclusions: Risk for latent coronary artery disease was similarly higher in smokers and smokeless tobacco dependence subjects.